Young Aboriginal women's voices on pregnancy care: Factors encouraging antenatal engagement. Issue 1 (March 2015) - Reibel, Tracy; Morrison, Lisa; Griffin, Denese; Chapman, Llinos; Woods, Heather
Abstract Background Rates of adolescent pregnancy in Australia have decreased over time for all population groups but for Aboriginal adolescents remain higher than their non-Aboriginal counterparts. There is limited literature identifying the motivations of young Aboriginal women to present for pregnancy care. Aim Understanding young Aboriginal women's views on pregnancy care is important knowledge to assist maternity services develop localised pathways that encourage engagement with pregnancy care. Methods A descriptive qualitative study with data collected using a bi-cultural research approach and an interview method known as yarning, with data interpretation informed by first hand cultural knowledge and current evidence. Findings The sample included 28 young women and 56 senior women and service providers. Typical actions indicative of antenatal engagement included: female relatives directing young woman to pregnancy care; availability at Aboriginal Health Services or in public hospitals and community based settings of multidisciplinary teams (midwife/Aboriginal Health Worker and/or Grandmother Liaison Officer); and, a continuous relationship with known and trusted care providers. Factors such as relocation for childbirth may interrupt pregnancy care. Active measures such as providing appointment reminders and transport to and from appointments assists young women to maintain antenatal contact. Conclusion The role of female relatives in directing young women's engagement with pregnancy care is crucial combined with availability of known and trusted care providers. Relocation from a home community to the nearest birth facility, and associated accommodation and transport options, are causes of concern requiring health system changes which more fully support culturally safe maternity options regardless of location.